Isotherm behaviour of p3OT, P3HT and PCBM Langmuir layer on ionic subphase - Naning, Fatin Hana; Syed Abdul Malik, .; Hanafi, Hafizul Fahri (Semarak Ilmu Publishing, 2023)
Isotherms are generally curves that depict the phenomena that govern a substance’s mobility at a constant temperature and pH. In this study, the Langmuir layer of P3OT, P3HT and PCBM were characterised by computing their surface pressure as a function of the surface area available to the molecules at the interface to obtain a curve called surface pressure – area (Π-A) isotherm. All three polymers were spread on two types of subphases - DI water and water containing bivalent metal ions, Pb2+. None of the Langmuir layers exhibits discrete gas-liquid-solid phase transitions on the water subphase. However, more stable Langmuir layers formed when lead ions were added to the water subphase. The stability enables the capping of lead ions between the polymer chain or within the balls, which can be implemented in flexible electronic devices.